Differential Use of Pediatric Video Visits by a Diverse Population During the COVID-19 Pandemic: A Mixed-Methods Study - Rosenthal, Jennifer L.; O'Neal, Christina; Sanders, April; Fernandez y Garcia, Erik (Frontiers in Pediatrics, 2021)
To describe and explore pediatric ambulatory video visit use by patient characteristics during the coronavirus disease 2019 (COVID-19) pandemic. We conducted an explanatory sequential mixed methods study with integration at the design and methods level. Phase 1 was a cross-sectional analysis of general and specialty pediatric ambulatory encounters to profile the use of video visits by patient characteristics. We performed descriptive analyses for each variable of interest and estimated a multivariable logistic regression model to analyze factors associated with the odds of having a video visit. Phase 2 was a qualitative exploration using semi-structured interviews with healthcare team members to understand the contextual factors influencing video visit usage. We used an interview guide to solicit information related to general perceptions about ambulatory video visits, reactions to the quantitative phase data, and strategies for optimizing equitable reach of video visits. Data were analyzed using a combination of deductive and inductive analysis. Among the 5,464 pediatric ambulatory encounters completed between March 11 and June 30, 2020, 2,127 were video visits. Patient factors associated with lower odds of having a video visit rather than an in-person visit included being Spanish-speaking (aOR 0.27, 95% CI 0.20–0.37) and other non-English-speaking (aOR 0.50, 95% CI 0.34–0.75) in comparison to English-speaking. Patients with public insurance also had a lower odds of having a video visit in comparison to privately insured patients (aOR 0.77, 95% CI 0.67–0.88). Qualitative interviews identified five solution-based themes: (1) Promoting video visits in a way that reaches all patient families; (2) Offering video visits to all patient families; (3) Mitigating digital literacy barriers; (4) Expanding health system resources to support families’ specific needs; and (5) Engaging and empowering health system personnel to expand video visit access. We identified differences in video visit use by patient characteristics, with lower odds of use among non-English-speaking and publicly insured patients. The mixed-methods approach allowed for the perspectives of our interview participants to contextualize the finding and lead to suggestions for improvement. Both our findings and the approach can be used by other health systems to ensure that all patients and families receive equal video visit access.